Digital audio. Interface for non-linear PCM encoded audio bitstreams applying IEC 60958. Non-linear PCM bitstreams according to the MPEG-4 Audio Lossless Coding (ALS) format Part 10, (31st July 2011) - British Standards Institution,
No abstract available